The Beneficial Effect of the COVID-19 Vaccine Booster Dose among Healthcare Workers in an Infectious Diseases Center - Agata Skrzat-Klapaczyńska; Carlo Bieńkowski; Justyna Kowalska; Marcin Paciorek; Joanna Puła; Dominika Krogulec; Jarosław Stengiel; Agnieszka Pawełczyk; Karol Perlejewski; Sylwia Osuch; Marek Radkowski; Andrzej Horban (Vaccines, 2022)
Introduction: Healthcare workers in Poland received a booster dose of the BNT162b2 mRNA vaccine (Pfizer-BioNTech, Manufacturer: Pfizer, Inc., and BioNTech; Moguncja, Germany) at the beginning of October 2021. Here, we report on the preliminary results of an ongoing clinical study into the antibody response to SARS-CoV-2 of healthcare workers previously exposed to the virus, with or without evidence of past infection, in the Hospital for Infectious Diseases in Warsaw before and after the vaccine booster dose. Methods: Blood samples were collected on the day the vaccine booster dose was administered and again 14 days later. The levels of SARS-CoV-2 IgG antibodies (against the n-protein, indicative of disease) and S-RBD (indicative of a response to vaccination) were measured. Results: One hundred and ten health care workers from the Hospital for Infectious Diseases were included in the study. The percentage of subjects with a positive test for anti-n-protein IgG antibodies at both time points remained unchanged (16, 14%), while a statistically significant increase in the percentage of subjects producing high levels of S-RBD antibodies (i.e., >433 BAU/mL) was observed (from 23, 21% to 109, 99%; p = 0.00001). Conclusions: The results of the study indicate that the booster dose of the vaccine significantly increases the percentage of people with high levels of S-RBD antibodies, regardless of previous contact with the virus, which may indicate greater protection against both the disease and a severe course of COVID-19.